Mediación y resistencia en procesos contratación: el rol bisagra de los seleccionadores de personal (2020)
The literature on inequality in the labor market has extensively documented the existence of discriminatory biases in selection processes. One of the aspects addressed about this phenomenon has been how organizations promote or facilitate the reproduction of these biases. In particular, it has been observed how, through the hiring decisions made by actors involved in personnel selection processes, such reproduction is materialized and doors of employment opportunity are closed. However, the same attention has not been paid to those actors who, in the midst of an organizational context crossed by discriminatory biases, decide not to reproduce them. In this sense, the purpose of this research is to analyze the factors that allow such a decision to be made. To this end, 16 in-depth interviews and a resume evaluation exercise were conducted with managers, chiefs and analysts from the human resources area of different companies in Bogotá. Based on the information obtained, it is argued that the probability that a recruiter will allow access to an applicant, who would otherwise be excluded due to bias, depends on the organizational culture in which he or she is found and his or her perception of freedom of movement in the labor market. This finding broadens the discussion on the characterization that the sociological literature has already made of the hiring processes and the decisions of the actors involved, showing small but important opportunities for agency in the processes of reproduction of inequalities.